2007
DOI: 10.1159/000111460
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormones Modify Reception of Species-Typical Communication Signals in a Female Anuran

Abstract: In many vertebrates, the production and reception of species-typical courtship signals occurs when gonadotropin and gonadal hormone levels are elevated. These hormones may modify sensory processing in the signal receiver in a way that enhances behavioral responses to the signal. We examined this possibility in female túngara frogs (Physalaemus pustulosus) by treating them with either gonadotropin (which elevated estradiol) or saline and exposing them to either mate choruses or silence. Expression of an activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 100 publications
4
32
0
Order By: Relevance
“…In turn, hormone levels affect behavioral responses to communication signals in frogs, fish, birds, reptiles and mammals (Adkins-Regen, 2005). In the case of acoustic communication, the reception of signals themselves can be influenced by hormones, as hormones have been shown to increase immediate early gene and electrophysiological responses in the auditory system (Arch and Narins, 2009;Lynch and Wilczynski, 2008;Maney and Pinaud, 2011;Penna et al, 1992;Yoder and Vicario, 2012). Here, we found that the responsiveness of the auditory midbrain to acoustic communication signals can be similarly enhanced by chronic exposure to dynamic conspecific signals.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…In turn, hormone levels affect behavioral responses to communication signals in frogs, fish, birds, reptiles and mammals (Adkins-Regen, 2005). In the case of acoustic communication, the reception of signals themselves can be influenced by hormones, as hormones have been shown to increase immediate early gene and electrophysiological responses in the auditory system (Arch and Narins, 2009;Lynch and Wilczynski, 2008;Maney and Pinaud, 2011;Penna et al, 1992;Yoder and Vicario, 2012). Here, we found that the responsiveness of the auditory midbrain to acoustic communication signals can be similarly enhanced by chronic exposure to dynamic conspecific signals.…”
Section: Discussionsupporting
confidence: 51%
“…female phonotaxis and male antiphonal calling behavior (Diekamp and Gerhardt, 1995;Gerhardt, 1974;Gerhardt, 1981a;Gerhardt, 1981b;Gerhardt, 1991;Simmons et al, 1993) mate attraction signals -and synthetic stimuli with similar spectral-temporal features are processed selectively or with enhanced responsiveness by neurons in many brain regions [as revealed in electrophysiology studies (Diekamp and Gerhardt, 1995;Eggermont and Epping, 1986;Elliott et al, 2011;Fuzessery and Feng, 1983;Miranda and Wilczynski, 2009a;Miranda and Wilczynski, 2009b;Rose et al, 1985) and immediate early gene studies (Chakraborty et al, 2010;Hoke et al, 2004;Hoke et al, 2008;Lynch and Wilczynski, 2008;Mangiamele and Burmeister, 2011)]. In anuran amphibians, this is particularly apparent in the midbrain (reviewed in Rose and Gooler, 2007;Wilczynski and Ryan, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that the plasma levels of gonadal steroids impact a variety of social behaviors, including the perception of, and responsiveness to, sociosexual signals (Sisneros et al, 2004;Maney et al, 2006;Lynch and Wilczynski, 2008). Such a role of sex steroid hormones in vertebrates results from activity within a "social behavioral network" that includes sexual motivational brain areas such as the medial preoptic area of the hypothalamus and the medial extended amygdala (Newman, 1999;Goodson, 2005).…”
Section: Regulation Of Plasticity-associated Gene Expression By Estramentioning
confidence: 99%